The harmonization of naqli and aqli approaches in affirming the Islamic creed in Dawud al-Fatani's Ward al-Zawahir - Mohamad, Hasbullah (IIUM Press, International Islamic University Malaysia, 2017)
This paper offers an examination of the scholarship of Dāwūd al-Faṭānī in dealing with the revealed sources (naqlī) and qualified scholarship in the exercise of the intellect (‘aqlī) in affirming the Islamic creed. The author emphasizes the determination of Dāwūd al-Faṭānī on the need to refer to the authority of naqlī and ‘aqlī so as to guard against deviation and exceeding the proper limits of methodological practices towards theological goal of knowing God (ma‘rifat Allāh). A qualitative methodology in which the textual analysis and comparative study was employed to analyse textual materials related to Dāwūd al-Faṭānī especially his writing, the Ward al-Zawāhir. Findings indicate that Dāwūd al-Faṭānī attempt ed to integrate the naqlī and ‘aqlī approaches, and harmonize such distinctions in dealing with theological approaches especially that of Salaf and Khalaf’s.